Assessing the impact of knowledge communication and dissemination strategies targeted at health policy-makers and managers: an overview of systematic reviews - Evelina Chapman; Tomas Pantoja; Tanja Kuchenmüller; Tarang Sharma; Robert F. Terry (BMC, 2021)
Abstract Background The use of research evidence as an input for health decision-making is a need for most health systems. There are a number of approaches for promoting evidence use at different levels of the health system, but knowledge of their effectiveness is still scarce. The objective of this overview was to evaluate the effectiveness of knowledge communication and dissemination interventions, strategies or approaches targeting policy-makers and health managers. Methods This overview of systematic reviews used systematic review methods and was conducted according to a predefined and published protocol. A comprehensive electronic search of 13 databases and a manual search in four websites were conducted. Both published and unpublished reviews in English, Spanish or Portuguese were included. A narrative synthesis was undertaken, and effectiveness statements were developed, informed by the evidence identified. Results We included 27 systematic reviews. Three studies included only a communication strategy, while eight only included dissemination strategies, and the remaining 16 included both. None of the selected reviews provided "sufficient evidence" for any of the strategies, while four provided some evidence for three communication and four dissemination strategies. Regarding communication strategies, the use of tailored and targeted messages seemed to successfully lead to changes in the decision-making practices of the target audience. Regarding dissemination strategies, interventions that aimed at improving only the reach of evidence did not have an impact on its use in decisions, while interventions aimed at enhancing users' ability to use and apply evidence had a positive effect on decision-making processes. Multifaceted dissemination strategies also demonstrated the potential for changing knowledge about evidence but not its implementation in decision-making. Conclusions There is limited evidence regarding the effectiveness of interventions targeting health managers and policy-makers, as well as the mechanisms required for achieving impact. More studies are needed that are informed by theoretical frameworks or specific tools and using robust methods, standardized outcome measures and clear descriptions of the interventions. We found that passive communication increased access to evidence but had no effect on uptake. Some evidence indicated that the use of targeted messages, knowledge-brokering and user training was effective in promoting evidence use by managers and policy-makers.